Customer Insight for Goodism Inc Future Product Development: A Laddering Approach - Ghifari, Muhammad; Iskandar, Budi Permadi (Journal of Business and Management, 2016)
Abstract. GOODISM Inc. is a startup business established on September 2013. GOODISM Inc. creates a unique and one-of-a-kind leather wallet with a focus on its main functions. As a new startup company, GOODISM Inc. should do rapid research and development to compete with the competitor. For the initial step, GOODISM Inc. is going to develop the direction to be more in line with the customer needs. Therefore, this research has objective to know the important factors of a wallet product based on consumer preference and to explore GOODISM Inc. target market core values by using the hierarchical value map. The study was conducted using laddering method in form of direct interview with the help of Mean-ends Chain Theory. Descriptive analysis used to explain the attributes come out from the interview result. The result of this study shows that the concrete attributes that customer want in a wallet are Size, Card Slot, Money Slot, Material, and Extra Slot. Moving to abstract attributes, the respondents pointed out three points of slim, unique, and elegant. For functional consequence, there are handy, pocketable, contain more items, well organized, and durable. As for psychological consequence, there are comfortable, practicality, safety, distinction, and pride that all leads to the values of self-confidence, self-fulfilment, and social recognition. By those results, the recommendation for GOODISM Inc. for its future development is to create big size compact wallet, small size compact wallet, and small size slim wallet. Keywords: Startup, Wallet, Means-end chain, Laddering approach, Customer insight